Environmental Sustainability of the Iron and Steel Industry: Towards Reaching the Climate Goals - Shatokha, Volodymyr (European Journal of Sustainable Development, 2016)
Radical modernization of the greenhouse gas emitting industrial sectors is indispensable for transition to a low-carbon economy. The iron and steel industry accounts for 6.7 % of the global anthropogenic carbon dioxide emissions. Futures of iron and steel industry based on various market penetration scenarios for best available and innovative technologies have been modelled and analyzed against the climate change mitigation targets identified by the International Energy Agency for keeping the global warming within 2°C. Plausible modernization pathways have been studied revealing a possibility of achieving the levels of CO2 emissions consistent with the climate targets by 2030-2040. However, reaching of the targets established for 2050 requires disruptive innovations in a synergy with carbon capture and storage/utilization, enhanced material efficiency and greater share of recycled steel production. The need for international collaboration to facilitate development and commercialisation of eco-innovations has been revealed. International instruments shall be applied in order to deliver incentive for modernisation, to boost carbon investment mechanisms and to ensure borderless technology transfer.